Penggunaan Media Sosial dalam Meningkatkan Keterampilan Menulis Opini Siswa Kelas VI SDN Merjosari 3 Kota Malang: The Use of Social Media in Enhancing Opinion Writing Skills of Sixth Grade Students at SDN Merjosari 3, Malang City - Wicaksono, Antonius Alam (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
This study aimed to enhance the opinion writing abilities of sixth-graders at SDN Merjosari 3, Malang City, by leveraging Instagram as a learning platform. Twenty students participated in a two-cycle study. Initially, the average student score was 72.5, with six students falling short of the minimum competency standards. This suggested that many students struggled with constructing arguments and expressing their views logically. In the second cycle, the focus shifted to using Instagram's comment feature to provide feedback on students' writing. Additionally, students were tasked with creating brief reels to present their opinions. Following this intervention, the average score rose to 85, with only two students not meeting the standard. These findings indicate that Instagram can effectively improve students' opinion writing skills. Students became more engaged, more confident in sharing their perspectives, and produced better-structured, more substantial writing. Instagram was selected due to its interactive features that facilitate visual sharing of written work.